Floor space covered by broiler chickens kept at stocking densities according to Council Directive 2007/43/EC. (30th July 2016) - Giersberg, M. F.; Hartung, J.; Kemper, N.; Spindler, B.
Abstract : It is controversially discussed whether the stocking densities set by the EU Directive 2007/43/EC allow a species‐appropriate housing of broiler chickens. To calculate the exact area broilers occupy due to their physical size and shape, planimetric measurements using a colour‐contrast method were carried out. In total, 1949 photographs of standing and 1482 of squatting chickens, taken from a top view, were analysed. A computer program counted the pixels representing the previously weighed animal in the photograph and calculated the animal area. The average area covered by chickens with 400 g live weight was 116.64±13.12 cm 2 in a standing and 138.61±12.92 cm 2 in a squatting position. These areas increased linearly as a function of live weight to 452.57±58.89 cm 2 (R 2 =0.90 standing) and 513.54±42.70 cm 2 (R 2 =0.82 squatting) at the end of the study (3200 g live weight). Squatting chickens occupied more space compared with a standing position in most of the tested weight classes (P<0.05). Depending on target weights, stocking densities and body positions, broilers occupied 48.5–77.7 per cent of 1 m 2 . Thus, from a physical point of view, simultaneous resting is possible at any stocking density provided by the EU Directive and at common target weights.